﻿Peculiar features of bone marrow cell proliferation in Djungarian hamsters with genetic disorders under thiotepa effect - Sergey Kuzin; Denis Bogomolov; Iza Berechikidze; Svetlana Larina; Tatyana Sakharova (Pensoft Publishers, 2022)
The paper aims to examine the proliferation of bone marrow cell pool in Djungarian hamsters and the subsequent restoration of their genetic stability after the action of thiotepa (TT). The study involved 36 animals, of which 16 were in the control group (injected with 0.25 ml of physiological solution), and 20 in the experimental group (0.25 ml of thiotepa at a dose of 1.5 mg per 1 kg of body weight). The maximum number of cells with CA amounting to 30.0% was observed 13 hours after TT injection (p≤0.05 between the control and experimental groups) and rapidly declined to 5.7% over subsequent periods by the 37th hour of the experiment (p≤0.05). The results suggest that the restoration of cell pool genetic stability is largely associated with the cell selection mechanisms, which confers an advantage over cell proliferation without chromosome anomalies.